Designing rich information experiences to shape learning outcomes. Issue 12 (2nd December 2017) - Maybee, Clarence; Bruce, Christine Susan; Lupton, Mandy; Rebmann, Kristen
Abstract : Students in higher education typically learn to use information as part of their course of study, which is intended to support ongoing academic, personal and professional growth. Informing the development of effective information literacy education, this research uses a phenomenographic approach to investigate the experiences of a teacher and students engaged in lessons focused on exploring language and gender topics by tracing and analyzing their evolution through scholarly discourse. The findings suggest that the way learners use information influences content-focused learning outcomes, and reveal how teachers may enact lessons that enable students to learn to use information in ways that foster a specific understanding of the topic they are investigating.